On further species of the spider genus Clubiona Latreille, 1804 (Araneae, Clubionidae) from Xishuangbanna Rainforest, southwestern China - Yu, Hao; Li, Shuqiang (Zootaxa, 2019)
A further study of the spider genus Clubiona Latreille, 1804 from Xishuangbanna, Yunnan, China is presented. A total of ten species, eight of which new to science, are here addressed, raising from 18 to 27 the number of species of the genus known to the area. Clubiona didentata Zhang & Yin, 1998 is redescribed based on new specimens from type locality, with the first description of the female. C. kai Jäger & Dankittipakul, 2010 is newly recorded from China, and the female is reported for the first time. Seven of the new species here described belongs to four species groups: C. cochlearis sp. nov. (♂) and C. tiane sp. nov. (♂) from the C. corticalis species-group; C. tongi sp. nov. (♂♀) from the C. hystrix species-group; C. yueya sp. nov. (♂♀) and C. zhanggureni sp. nov. (♂) from the C. japonica species-group; and C. bicornis sp. nov. (♂) and C. subasrevida sp. nov. (♂♀) from the C. trivialis species-group. The eighth new species, C. jiandan sp. nov. (♂♀) is not readily assignable to any of the existing species groups.